Workers' participation in wage setting and opportnistic behaviour: Evidence from a gift-exchange experiment - Jörg Franke; Ruslan Gurtoviy; Vanessa Mertins (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
Our study analyzes the consequences of workers' participation in the wage setting process on effort exertion. The experimental design is based on a modified giftexchange game where the degree of workers' involvement in the wage setting process is systematically varied among the workers. The experimental data reveals that workers' participation leads actually to a decline in effort exertion which can be explained by negative reciprocity of the respective worker. These results put some recently observed positive effects from workers' participation in experimental labor markets into perspective and are more in line with the ambiguous results from empirical studies.
Keywords: C72; C91; J33; L23; M52; M55; 330; Participation; labor market; gift-exchange game; personnel economics; reciprocity